Bone density parathyroid hormone and 25-hydroxyvitamin D concentrations in middle aged women. Issue 6848 (1st August 1992) - Khaw, K. T.; Sneyd, M. J.; Compston, J.
Abstract : OBJECTIVE–To examine the relation between bone density and indices of calcium metabolism including parathyroid hormone and 25-hydroxyvitamin D concentrations in middle aged women. DESIGN–A cross sectional study. SETTING AND SUBJECTS–138 women volunteers aged 45-65 with no known osteoporosis and unselected for disease status recruited for a dietary assessment study from the community using general practice registers. Volunteer rate was 20%. MAIN OUTCOME MEASURE–Bone mineral density measured with dual energy x ray absorptiometry. RESULTS–Bone density at the lumbar spine and neck and trochanteric regions of the femur was inversely related to serum intact parathyroid hormone concentrations and positively related to serum 25-hydroxyvitamin D concentrations. These associations were independent of possible confounding factors, including age, body mass index, cigarette smoking habit, menopausal status, and use of diuretics and postmenopausal hormone replacement therapy. These associations were apparent throughout the whole distribution of bone density and 25-hydroxyvitamin D and parathyroid hormone concentrations within the normal range, suggesting a physiological relation. CONCLUSIONS–The findings are consistent with the hypothesis that parathyroid hormone and 25-hydroxyvitamin D concentrations influence bone density in middle aged women. Findings from this study together with other work suggest that the role of vitamin D in osteoporosis should not be neglected. The associations with parathyroid hormone also indicate plausible biological mechanisms. The roughly 5-10% difference in bone density between top and bottom tertiles of serum 25-hydroxyvitamin D concentrations, though not large in magnitude, may have considerable public health implications in terms of prevention of osteoporosis and its sequelae, fractures.